Healthy feet between theory and technique: (re)constructing Camper’s ideal shoe - Hendriksen, Marieke (Studium, 2018)
This article shows how the (re)construction of objects based on historical, textual sources can give us insight in how such sources may have functioned in their original context. In addition, they make us reflect critically on the development of their long-term reception history, and – through a ‘material turn’ in the history of science – can lead to a ‘historical turn’ in contemporary craft training. The connection of Camper’s 1799 text on shoemaking with the early modern obsession with regimen allowed it to retroactively become the theoretical foundation of a field that relied almost exclusively on practical, technical instruction and the development of material literacy until the early twentieth century.